Enhancing the Photovoltaic Performance of Triplet Acceptors Enabled by Side‐Chain Engineering. Issue 10 (8th September 2021) - Zhang, Xin; Qin, Linqing; Liu, Xingzheng; Zhang, Caixia; Yu, Jianwei; Xiao, Zuo; Zheng, Nan; Wang, Boxuan; Wei, Yanan; Xie, Zengqi; Wu, Yishi; Wei, Zhixiang; et al.
Abstract : Triplet excitons have both longer lifetimes and diffusion lengths than singlet excitons due to the nature of triplet excitons, which is expected to increase the photocurrent and further improve the performance of organic solar cells (OSCs). However, the working mechanism of triplet excitons in OSCs is not clearly clarified. Therefore, it is urgent to develop new triplet acceptors for in‐depth understanding. Herein, a series of acceptors (BT n ‐4Cl ) are synthesized by fine‐tuning of the side‐chain branch positions. The generation of triplet excitons of BT n ‐4Cl is confirmed by the time‐resolved photoluminescence (TRPL) spectra, magnetophotocurrent (MPC) experiment, and electron paramagnetic resonance (EPR) spectra. The effects of side‐chain engineering on the optoelectronic properties, packing behaviors, energy losses, charge transport properties, spin lifetimes of triplet polarons, and blend film morphologies are systematically studied. These results show that D18:BT3‐4Cl ‐based OSCs possess the best power conversion efficiency (PCE) of 17.31% due to lower energy losses, less recombination losses, more balanced charge carrier mobilities, longer spin–lattice ( T 1 ) relaxation time, and more favorable morphology. This work enhances the understanding of the structure–property relationship for high‐performance triplet acceptors. Abstract : A series of triplet acceptors are synthesized via regulating the alkyl side chains. The effects of side‐chain engineering on the optoelectronic properties, packing behaviors, triplet properties, energy losses, charge transport properties, spin lifetimes of triplet polarons, blend film morphologies, and overall photovoltaic performance are systematically studied. This work enhances the understanding of the structure–property relationship for high‐performance triplet acceptors.